Inherited ichthyoses: molecular causes of the disease in Czech patients - Borská, Romana; Pinková, Blanka; Réblová, Kamila; Bučková, Hana; Kopečková, Lenka; Němečková, Jitka; Puchmajerová, Alena; Malíková, Marcela; Hermanová, Markéta; Fajkusová, Lenka (Orphanet journal of rare diseases, 2019)
Inherited ichthyoses belong to a large and heterogeneous group of mendelian disorders of cornification, and can be distinguished by the quality and distribution of scaling and hyperkeratosis, by other dermatologic and extracutaneous involvement, and by inheritance. We present the genetic analysis results of probands with X-linked ichthyosis, autosomal recessive congenital ichthyosis, keratinopathic ichthyosis, and a patient with Netherton syndrome. Genetic diagnostics was complemented by in silico missense variant analysis based on 3D protein structures and commonly used prediction programs to compare the yields of these two approaches to each other. This analysis revealed various structural defects in proteins coded by mutated genes while no defects were associated with known polymorphisms. Two patients with pathogenic variants in the ABCA12 gene have a premature termination codon mutation on one allele and a silent variant on the second. The silent variants c.69G > A and c.4977G > A are localised in the last nucleotide of exon 1 and exon 32, respectively, and probably affect mRNA splicing. The phenotype of both patients is very severe, including a picture harlequin foetus after birth; later (at 3 and 6 years of age, respectively) ectropin, eclabion, generalised large polygonal scaling and erythema.
Keywords: In silico analysis; Genetic Predisposition to Disease; Phenotype; Codon, Nonsense; ABC transportéry; Ichthyosis; nesmyslný kodon; Humans; genetická predispozice k nemoci; Autosomal recessive congenital ichthyosis; fenotyp; ATP-Binding Cassette Transporters; Czech Republic; 3D protein structure; lidé; Keratinopathic ichthyosis; ichtyóza; Česká republika